2002
DOI: 10.1001/jama.288.16.2015
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Risk of Ischemic Heart Disease and Stroke

Abstract: This meta-analysis of observational studies suggests that elevated homocysteine is at most a modest independent predictor of IHD and stroke risk in healthy populations. Studies of the impact on disease risk of genetic variants that affect blood homocysteine concentrations will help determine whether homocysteine is causally related to vascular disease, as may large randomized trials of the effects on IHD and stroke of vitamin supplementation to lower blood homocysteine concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
312
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,830 publications
(324 citation statements)
references
References 60 publications
9
312
0
3
Order By: Relevance
“…This magnitude of tHcy-lowering effect is consistent with the projected average treatment effect of a 4.0 µmol/l reduction with folic acid-based multivitamin therapy that has been previously demonstrated [9], and should ensure adequate statistical power to reliably identify an expected reduction in risk of the composite outcome of stroke, myocardial infarction and vascular death of at least 15% [7, 10, 11]. However, this also requires that a similar magnitude of treatment effect is maintained throughout the duration of the trial, despite increasing voluntary folic acid fortification of food in Australia and other countries in which the VITATOPS trial is being conducted.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…This magnitude of tHcy-lowering effect is consistent with the projected average treatment effect of a 4.0 µmol/l reduction with folic acid-based multivitamin therapy that has been previously demonstrated [9], and should ensure adequate statistical power to reliably identify an expected reduction in risk of the composite outcome of stroke, myocardial infarction and vascular death of at least 15% [7, 10, 11]. However, this also requires that a similar magnitude of treatment effect is maintained throughout the duration of the trial, despite increasing voluntary folic acid fortification of food in Australia and other countries in which the VITATOPS trial is being conducted.…”
Section: Introductionsupporting
confidence: 81%
“…A recent systematic review of individual patient data from 30 prospective and retrospective studies involving a total of 5,073 coronary events and 1,113 stroke events indicated that, after adjusting for confounding caused by known vascular risk factors and correction for regression dilution caused by random variation in homocysteine measurements, a 25% lower usual tHcy concentration in the blood [about 3 µmol/l (0.41 mg/l)] was associated with an 11% (OR 0.89, 95% CI 0.83–0.96) lower risk of a coronary event, and a 19% (OR 0.81, 95% CI 0.69–0.95) lower stroke risk [10]. Concurrently, another recent systematic review of 20 prospective studies (involving 3,820 participants) of serum homocysteine and disease risk concluded that lowering homocysteine concentrations by 3 µmol/l from current levels (achievable by increasing daily intake of about 0.8 mg folic acid) would reduce the risk of stroke by 24% (95% CI 15–33%) and ischemic heart disease by 16% (11–20%) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate folate intake constitutes a leading cause of folate deficiency, which involves decreased serum or plasma folate concentrations followed by increased serum or plasma total homocysteine (tHcy) concentrations and reduced red blood cell (RBC) folate levels. Elevated tHcy represents a major risk factor of cardiovascular and cerebrovascular diseases (Homocysteine Studies Collaboration 2002). Moreover, lower serum folate and higher plasma tHcy may also be causes of neural tube defects (NTDs) (Smithells et al 1976; Daly et al 1995), cognitive dysfunction (Seshadri et al 2002), and depression (Bottiglieri 2005).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are studies showing an increased risk of arterial thrombotic complication in patients with VTE (7). The role of inherited thrombophilia in ATE is less clear but hyperhomocysteinemia, inherited or acquired, has been demonstrated to be an independent risk factor for atherothrombosis (8). Two polymorphisms of the methylenetetrahydrofolate reductase (MTHFR) gene -C677T and A1298C -are the most common inherited causes of hyperhomocysteinemia.…”
Section: Thrombophilia Genetic Testing In Romanian Young Womenintrodumentioning
confidence: 99%